AKTIVITAS ANTIOKSIDAN DAN SIFAT SENSORIS STIK BUAH NAGA MERAH (Hylocereus Polyrhizus) - Supriyanto Supriyanto (Agroindustrial Technology Journal, 2022)
and Red dragon fruit has higher properties, namely carotene and flavonoids which are antioxidants that are good for the body to consume to help neutralize free radicals that attack the body's cells. One of the problems with dragon fruit is the high stock of dragon fruit during the harvest but consumer demand is relatively fixed so that the price of dragon fruit is decreasing. Dragon fruit can be used as a variety of delicious and highly nutritious preparations that have. This study was conducted to find out the antioxidant activity, color, moisture content, texture and sensory by using 3 comparisons of dragon fruit concentration and dragon fruit stick cooking temperature. The concentration of dragon fruit used is 0%, 15% and 30%, while the temperature used is 150oC and 160oC. From the results of this study obtained the results of dragon fruit variation treatment have a real effect on the antioxidant activity, sensory aroma, color, texture, taste and overall dragon fruit sticks. The treatment of temperature variations can have a real influence on water content, L color (lightness), color a (redness), sensory texture, taste and overall dragon fruit sticks. The interaction between dragon fruit and temperature (Dragon fruit*temperature) has a real effect on the texture of cohesiveness, sensory texture, taste and overall dragon fruit sticks